Altered 8-oxoguanine glycosylase in mild cognitive impairment and late-stage Alzheimer's disease brain - Shao, Changxing; Xiong, Shuling; Li, Guo-Min; Gu, Liya; Mao, Guogen; Markesbery, William R.; Lovell, Mark A. (Free radical biology & medicine, 2008)
Eight-hydroxy-2′-deoxyguanosine (8-OHdG) is increased in the brain in late-stage Alzheimer's disease (LAD) and mild cognitive impairment (MCI). To determine if decreased base-excision repair contributes to these elevations, we measured oxoguanine glycosylase 1 (OGG1) protein and incision activities in nuclear and mitochondrial fractions from frontal (FL), temporal (TL), and parietal (PL) lobes from 8 MCI and 7 LAD patients, and 6 age-matched normal control (NC) subjects. OGG1 activity was significantly ( P < 0.05) decreased in nuclear specimens of FL, TL, and PL in MCI and LAD and in mitochondria from LAD FL and TL and MCI TL. Nuclear OGG1 protein was significantly decreased in LAD FL and MCI and LAD PL. No differences in mitochondrial OGG1 protein levels were found. Overall, our results suggest that decreased OGG1 activity occurs early in the progression of AD, possibly mediated by 4-hydroxynonenal inactivation and may contribute to elevated 8-OHdG in the brain in MCI and LAD.